Perancangan Baru Interior Rumah Singgah Kanker Anak Ykaki Di Cilandak Jakarta Dengan Pendekatan Paliatif - Ammara Purwaningrum, Kinanti; Friestya Asharsinyo, Doddy; Salayanti, Santi (Telkom University, 2024)
Cancer is the 2nd deadly disease in the world where in Indonesia there are 877,531 cases and there are around 209,236 children diagnosed with cancer in 2023. This happens because more than 50% of cancer cases in children come to health facilities in an advanced stage, due to the factor that the majority of pediatric cancer hospitals are in big cities like Jakarta, so it requires a large amount of money for treatment. A halfway house is a facility specitically designed to create a comfortable and safe place to stay, providing emotional, social, spiritual support to children and caregivers of patients who are undergoing cancer treatment outside the city without any costs that need to be incurred by the family. Patients and families who have a diagnosis of a disease with minimal cure rates have a sense of low fighting spirit, so palliative care was formed with the aim of improving the quality of life of patients and families in dealing with problems related to life-threatening diseases which are generally aimed at patients with high mortality rates, one of which is cancer. Creating an optimistic interior atmosphere for recovery is one of the things that can be done by applying palliative principles in an interior, by providing a sense of comfort, calm, not passive, and by applying natural elements in it. Keyword : interior design, shelter, palliative